Analysis and Optimization of Dynamic Characteristic of Automobile Transmission Test Bench based on Time Domain and Frequency Domain - Ji Yunlong; Zou Xihong; Shi Xiaohui; Gou Xun (Jixie chuandong)
The dynamic characteristic is one of the most important performances of the dynamic simulation test bench for automobile transmission. Combining with the CATIA,ADAMS and MATLAB,the multi- body dynamics equation and the dynamics model of the transmission test bed are established. On these foundations,the dynamic response evaluation index of the transmission test bench in the time domain is presented. The dynamic response multi- objective optimization model of the transmission test- bed is established with the evaluation index of rise time,stability time and overshoot,and the simulation analysis and optimization are carried out. Otherwise,the dynamic response model of the transmission test bench is established and the dynamic response is analyzed and optimized in the frequency domain. The results show that the smaller the rotational inertia of the system,the bigger the rigidity and the damping ratio is conducive to the dynamic characteristics of system. Compared with the pre- optimization,the overshoot is reduced by 19. 1%,rise time decreases by5. 56%,peak time decreased by 17%,stable time decreased by 40. 7%,the dynamic characteristic of the system is greatly improved.